Pension Developments and Reforms in Transition Economies - Cottarelli, Carlo; Cangiano, M.; Cubeddu, Luis. (Washington, D.C. : International Monetary Fund, 1998)
This paper reviews developments in pension systems in 11 transition economies during the 1990s, highlighting the forces behind their rapid weakening. It focuses on the challenges these systems face-including those arising from demographic factors-and discusses why most transition countries are considering shifting, or have already shifted, from traditional defined-benefit pay-as-you-go systems to defined-contribution fully funded systems. Finally, the paper looks at the main options that arise in introducing fully funded components, including the relative mix between funding and pay-as-you-go, and the speed of the transition toward the new system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet